Course advisor system - Ahlan, Abdul Rahman; Ahmad, Nur Farhana (IIUM Press, 2011)
The Course Advisor System is presented in this chapter. The system mainly serves for students who mainly majoring in BIT, for both local and international students. The system will act as a guide to help students in making decision of choosing courses to register for each semester. The system first will display student personal infonnation. and then display student academic infonnation. This is all the detail infonnation about a particular student that stored in the department database. After that, the system will automatically generate the study plan base on individual. The Course Advisor System will suggest consecutive courses to be taken by students to ensure progress toward completing degree requirements. Students usually make wrong decision in choosing courses to register and they do not have any plan ahead for their study. Therefore, the Course Advisor System will help them to do that